PengaruhBrand Image, Kualitas Produk Dan Harga Terhadap Minat Beli Produk Oriflame (Studi Kasus Pada Mahasiswa di Universitas Hasyim Asy’ari Jombang) - Cici Suasti Ningsih; Lik Anah (BIMA : Journal of Business and Innovation Management, 2021)
This study aims to determine the effect of brand image, product quality and price on buying interest in Oriflame products (case study of students at Hasyim Asyari University, Jombang). The background of this research is a decrease in the level of sales in various types of products owned by Oriflame products. With various types of cosmetics offered, domestic and foreign products. The independent variable in this study is brand image, quality of product and price while the independent variable is buying interest. The method used in this research is quantitative and uses associative research methods. The number of samples as many as 100 people using purposive sampling techniques. The technique of collecting data uses a questionnaire in order to guarantee validity and reliability. The hypothesis will be issued using multiple regression analysis and the results of this study indicate that Brand Image has a significant effect on the purchase interest of Oriflame products, the quality of the product is significant on the purchase interest of Oriflame products and the price has a significant effect on the purchase interest of Oriflame products. Keywords: Brand Image, Quality of product and Price